Analysis of science laboratory facilities at Junior High School Bina Ilmi, Palembang City, Indonesia - Muhammad Julian; Astrid Sri Wahyuni Sumah (Jurnal Pijar Mipa, 2023)
One of the facilities in the teaching and learning process that should be considered is the laboratory. The laboratory is an effective learning resource to achieve the expected competencies for students in increasing efficiency and effectiveness; the laboratory must be managed and utilized correctly. Science learning is not just theory; it is necessary to carry out practical activities in the laboratory. Following Permendiknas No 24 of 2007, laboratory facilities and infrastructure are needed to support practicum activities. This study aims to determine the carrying capacity of the science laboratory facilities at SMP IT Bina Ilmi Palembang and determine the obstacles faced in conducting practicums at the science laboratory at SMP IT Bina Ilmi Palembang. This study uses descriptive qualitative research. The results showed that most science laboratory facilities in schools needed to meet the standards of Permendiknas No. 24 of 2007. There were many areas for improvement in the availability of practicum equipment and media that could support practicum implementation activities to increase student learning outcomes. Obstacles that affect practicum activities are the lack of ability to manage school laboratories, lack of understanding of the meaning and function of school laboratories and their implications for the development and improvement of science learning systems, the limited ability of teachers to master subjects, and uneven procurement and distribution of Science Kit teaching aids so that makes it difficult for the teacher activity center to carry out its coaching function for teachers. Ironically, the existence of a school laboratory is considered a burden, so it is rarely used correctly.